Two-Dimensional Infrared Spectroscopy and Molecular Dynamics Simulation Studies of Nonaqueous Lithium Ion Battery Electrolytes - Lim, Joonhyung; Lee, Kyung-Koo; Liang, Chungwen; Park, Kwang-Hee; Kim, Minjoo; Kwak, Kyungwon; Cho, Minhaeng (The journal of physical chemistry. B, 2019)
Lithium ion battery (LIB) technology is undoubtedly indispensable to modern life. However, despite enormous and extended effort to improve LIB performance, our understanding of the underlying principles and mechanisms of lithium ion transport in nonaqueous LIB electrolytes remained limited until recently. There is a particular lack of knowledge of the microscopic solvation structures and fluctuation dynamics around charge carriers in real electrolytes. Typical electrolytes found in commercially available LIBs consist of lithium salts and mixed carbonate solvents, with the latter playing an essential role in promoting lithium ion transport and forming an electrically stable solid electrolyte interphase. Although a number of linear spectroscopic studies of LIB electrolytes aiming at understanding the complex nature of lithium ion solvation processes have been reported, the notion that each lithium ion is strongly solvated by carbonate molecules to form a long-lasting solvation sheath structure has remained the subject of intense debate. Here, we present the results of FTIR, fs IR pump-probe, two-dimensional IR spectroscopy, and molecular dynamics simulations reported by us and others and discuss the possible interplay of picosecond solvation dynamics and macroscopic ion transport processes within the framework of the fluctuation-dissipation relationship. Further, by measuring the time-dependent fluctuations and spectral diffusions of carbonate carbonyl stretch modes that act as excellent infrared probes for the local electrostatic environment, we show that lithium cations are not only solvated by carbonate molecules but also interact with counteranions at equilibrium depending on solvent composition. Molecular dynamics simulations support the notion that rapid chemical exchanges between carbonate solvent molecules in the first and outer solvation shells are critical for describing mobile lithium ion transport phenomena. We thus anticipate that time-resolved coherent multidimensional vibrational spectroscopy is capable of providing decisive evidence on the ultrafast solvent dynamics of various electrolytes, which is potentially helpful for designing improved and more efficient LIB electrolytes in the future.